(3JgPjH GdCSQGQ aj WHbGJ GdCNjGQs - (3YHO Gdedc Hf eMeO Hf EHQGgje GdfjSGHhQj GdNQchTj, CHh SYO,J (B407 (3g` s ((3OGhO Hf Ydi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi dGJMSf GdCTjGA EdG Cf jchf gh ChdgG s
(3BNQgG (B:s
(3hQhi CHh HcQ GdUOjb QVi Gddg Yfg ai GdefGe abjd dg (B: (3Gfc cfJ Jbhd CHOkG ai dSGfc (B: (3Ef gPG ChQOfi GdehGQO , aeG aYd Gddg Hc bGd bdJ dg (B: (3dG Edg EdG Gddg , aChQOfi GdLfI Je cJGH JgPjH GdCSQGQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi MhGTjgG HYV GdJYdjbGJ hebGHdGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs